Photocatalytic Degradation of Polyethylene Microplastics and Disinfection of E. coli in Water over Fe- and Ag-Modified TiO2 Nanotubes - Yuwendi Yuwendi; Muhammad Ibadurrohman; Setiadi Setiadi; Slamet Slamet (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
In this study, Fe- and Ag-modified TiO2 nanotubes were synthesized via an anodization method as photocatalysts for degradation of polyethylene microplastics and disinfection of Escherichia coli (E. coli). The anodization voltage, as well as the Fe3+ or Ag+ concentrations on TiO2 nanotubes were evaluated and correlated to their corresponding photocatalytic properties. TiO2 nanotubes were firstly synthesized by anodization of Ti plates in a glycerol-based electrolyte, followed by incorporation of either Fe or Ag via a Successive Ionic Layer Adsorption and Reaction (SILAR) method with Fe(NO3)3 and AgNO3 as Fe and Ag precursors, respectively. UV-Vis DRS shows that the addition of Fe or Ag on TiO2 nanotubes causes a redshift in the absorption spectra. The X-ray diffractograms indicate that, in the case of Fe-modified samples, Fe3+ was successfully incorporated into TiO2 lattice, while Ag scatters around the surface of the tubes as Ag and Ag2O nanoparticles. A microplastic degradation test was carried out for 90 mins inside a photoreactor with UVC illumination. TiO2 nanotubes that are anodized with a voltage of 30 V exhibit the best degradation results with 17.33% microplastic weight loss in 90 mins. Among the modified TiO2 nanotubes, 0.03 M Ag-TiO2 was the only one that surpassed the unmodified TiO2 in terms of microplastic degradation in the water, offering up to 18% microplastic weight loss in 90 min. In terms of E. coli disinfection, 0.03M Ag-TiO2 exhibit better performance than its unmodified counterpart, revealing 99.999% bactericidal activities in 10 mins. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).